Bacterial activation of human natural killer cells: role of cell surface lipopolysaccharide - Lindemann, R A (Infection and immunity, 1988)
Culture of human peripheral blood lymphocytes with gram-negative bacteria associated with periodontal disease caused a rapid increase in the cytotoxic potential of natural killer (NK) cells. The NK cells were activated to kill NK-resistant targets, the peak cytotoxicity occurring on day 1 of culture. The addition of anti-Tac, anti-CD3, or anti-OKT-11 antibodies to block activation via the interleukin-2 (IL-2), T-cell, or E rosette receptors had a minimal effect on this inductive process. Anti-IL-2 antiserum was effective in blocking a significant amount, but not all, of the cytotoxicity in bacterium-activated cultures. Modest IL-2 production (5 to 6 National Institutes of Health units) was measured in lymphocyte cultures activated by bacteria, but proliferation was not induced during a 1-week period. When polymixin B sulfate was added to bind and block lipopolysaccharides, bacterium-induced cytotoxicity was completely abrogated for all activating bacteria. In addition, when culture supernatants from Actinobacillus actinomycetemcomitans were tested, activation still occurred. However, again, this activation was totally inhibited by polymixin B sulfate. Monocytes were also activated by bacteria to produce tumor necrosis factor (TNF). To exclude the possibility that TNF was responsible for cytotoxicity, an antiserum to TNF was added to cocultures of bacteria and lymphocytes with adherent cells removed. The antiserum had no effect on the inductive process. In addition, exogenous TNF did not kill M14 targets. These results suggest that bacterial cell surface lipopolysaccharides provide a major activation signal for NK cells to enhance cytotoxicity.